Anti-diabetic and acute toxicity studies of Annona squamosa L. ethanolic leaves extract. - Farah - Saeed; Mansoor Ahmad (International Journal of Phytomedicine, 2017)
Aim of this research work was to explore the anti-diabetic activity and acute toxicity of Annona squamosa L. leaves ethanolic extract in albino rats and mice respectively. Diabetes was induced by Alloxan (120 mg/kg). Seven rats were taken in each group. Glibenclaimide (0.25 mg/kg) was taken as the standard drug. A. squamosa was administered orally in 100mg, 200mg and 400mg doses in three different groups of diabetes- induced rats. A. squamosa leaves extracts were found to have significant anti-diabetic activity. Acute toxicity study was carried out on administration of 800mg/kg, 1600mg/kg and 5000 mg/kg body weight. No acute toxicity was observed at 800mg/kg and 1600mg/kg doses. At 5000mg/kg body weight dose 100% fatality was recorded within 24 hours. Our research work revealed the safe and effective anti-diabetic activity of Annona squamosa ethanolic leaves extract.